Bilateral Trade Agreements and the Rise of Global Supply Chains in the Modern International Business - Zdzislaw W. Puslecki (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The main aim of the article is indication of the increasing importance of bilateral trade agreements in the foreign trade policy and the rise of global supply chains in the modern international business,. The subject of the discussion and theoretical contribution in the undertaken research program is presents new tendencies in international business - the rise of importance of bilateral agreements in foreign trade policy. It is important to underline that a few multinational firms are responsible for a major share of world trade and for the rise of global supply chains. On the one hand, these firms should support regulatory harmonization across different Preferential Trade Agreements (PTAs) in order to lower trade costs. On the other hand, they might also resist harmonization – and encourage certain non-tariff measures – in order to prevent new competitors from entering markets. This may partly explain the persistence of regulatory divergence, and suggests that the political economy of regulatory convergence, especially in the conditions of the rise global supply chains, may be more complex than is sometimes suggested.